Effectiveness of the application of acceptance and commitment group therapy in the complex treatment of patients with anxiety disorders and sleep disturbances - Zhyvotovska, Анастасія; Isakov, Рустам (Psychosomatic Medicine and General Practice, 2024)
The data of modern scientific research testify to the effectiveness of acceptance and commitment therapy (ACT) as the third wave of cognitive-behavioral therapy in the treatment of anxiety and depression. A positive effect on insomnia and sleep quality was found when applying the acceptance and commitment therapy method for working with insomnia (ACT-I). The purpose of the study was to evaluate the effectiveness of complex therapy of patients with neurotic anxiety disorders and sleep disorders using acceptance and commitment group therapy based on an integrated approach according to the ACT and ACT-I protocols. An examination of 91 patients with anxiety disorders of the neurotic origin and sleep disorders was carried out using clinical-psychopathological, clinical-anamnestic and psychodiagnostic methods. The study was conducted using the HADS scale, PSQI, SF-36, AAQ-II questionnairies, one-item sleep quality scale SQS. The respondents were divided into two groups: main group (MG) included 42 people who received acceptance and commitment group psychotherapy in combination with psychopharmacotherapy, and comparison group (CG) included 49 people who received only psychopharmacotherapy according to clinical guidelines. The groups did not have a statistically significant difference in age, sex, and clinical parameters. The dynamics of patients` psycho-emotional state, quality of sleep and quality of life were studied before and after 8 weeks of therapy. There was a decrease in the level of anxiety according to the HADS scale (p<0,01), a decrease in PSQI indicators such as the general index of sleep quality, «subjective sleep quality» and «daytime dysfunction» (p<0,001), «sleep latency», «sleep disturbance» and «use of sleep medication» (p<0,05), improvement of quality of life indicators on the scales «physical functioning», «bodily pain», «mental health» (p<0,05), «social functioning», «role emotional functioning» and «mental component summary» (p<0,01) in the MG, compared to the CG. The obtained data demonstrated a significant advantage of the developed complex therapy using an integrated approach of group therapy according to the AСT and AСT-I protocols in the treatment of patients with anxiety disorders of neurotic origin and sleep disorders compared to the standard approach. In the patients of the main group, there was a significant reduction in anxiety and depressive symptoms, improvement in indicators of sleep quality, quality of life and psychological flexibility, which confirms the effectiveness of the proposed treatment and rehabilitation measures.